2017
DOI: 10.1038/srep41575
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change of a Tryptophan Residue in BtuF Facilitates Binding and Transport of Cobinamide by the Vitamin B12 Transporter BtuCD-F

Abstract: BtuCD-F is an ABC transporter that mediates cobalamin uptake into Escherichia coli. Early in vivo data suggested that BtuCD-F might also be involved in the uptake of cobinamide, a cobalamin precursor. However, neither was it demonstrated that BtuCD-F indeed transports cobinamide, nor was the structural basis of its recognition known. We synthesized radiolabeled cyano-cobinamide and demonstrated BtuCD-catalyzed in vitro transport, which was ATP- and BtuF-dependent. The crystal structure of cobinamide-bound BtuF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
(55 reference statements)
7
28
0
Order By: Relevance
“…The structure was solved by MR using the same truncated version of TC that was used for the structure solving of apo TC-beta as search model. The ligand structure and geometry-restraints files were downloaded from PDB ID 5M29 [ 31 ]. In the structure of TC-beta:AntiB12 one calcium molecules was placed, coordinated by one His305 and its backbone amide, which is part of the flexible N-terminus, as well as by two water molecules and the surface exposed His345 of a symmetry mate.…”
Section: Methodsmentioning
confidence: 99%
“…The structure was solved by MR using the same truncated version of TC that was used for the structure solving of apo TC-beta as search model. The ligand structure and geometry-restraints files were downloaded from PDB ID 5M29 [ 31 ]. In the structure of TC-beta:AntiB12 one calcium molecules was placed, coordinated by one His305 and its backbone amide, which is part of the flexible N-terminus, as well as by two water molecules and the surface exposed His345 of a symmetry mate.…”
Section: Methodsmentioning
confidence: 99%
“…As a first step to assess the effect of the obtained nanobodies on BtuCD-F function, we determined the affinity of the selected nanobodies to BtuF and their ability to displace Cbl from BtuF. Cbl binding to BtuF was analyzed at pH 7.5 and 23 °C by measuring Cbl-induced fluorescence quenching of fluorescently labeled BtuF (BtuF fluo ), an assay developed and described previously 6 (Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…BtuF for the pull-down, crystallization, binding and transport assays, was prepared as described previously 6 , 18 . The Avi-tagged BtuF construct for the panning was cloned by insertion of a C-terminal Avi-tag between the BtuF gene and the 3 C cleavable His-tag.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, Locher et al. showed that one of the receptors (BtuCD‐F), which mediated Cbl uptake into E. coli , might also be involved in the uptake of cobinamide ( 2 ), which is a Cbl precursor that lacks the nucleotide loop . During the uptake process, vitamin B 12 binds to a series of receptors; therefore, alterations to the vitamin structure might have a profound effect on the extent of its uptake.…”
Section: Introductionmentioning
confidence: 99%